82 Near-Universal Active Surveillance for Small Renal Mass Patients: A Novel 12-Year Clinical Experience - Eric Kauffman (The Oncologist, 2026)
Abstract Background Surgical extirpation has long been the gold-standard management option for patients with clinically localized small renal masses (SRM, </= 4 cm). However, there is increasing awareness of SRM clinical indolence and hence overtreatment. Research on active surveillance (AS) as an alternative management option for SRM patients has been limited historically by selection bias for smaller SRM sizes and comorbid/elderly patients who are less fit for treatment. Hence, the oncologic safety and likelihood to require delayed intervention (DI) among healthier, unselected SRM patients who elect AS are unknown. Here we report outcomes from more than a decade’s experience with a novel clinical approach in which nearly all SRM patients were managed with AS rather than upfront treatment, including with no health-related selection bias. Methods From Jan 2013-Dec 2024, all nonhereditary SRM patients without dialysis dependency or prior RCC treatment history who presented to a single urologist at a National Comprehensive Cancer Center were recommended AS whenever predefined progression criteria for intervention (PCI) were absent. PCI were defined prospectively using clinical thresholds based on GLASS-acronym criteria (Growth rate, Longest tumor diameter (LTD), Adverse biopsy histology, Stage (cT), Symptomatology). Renal mass biopsy was performed routinely for SRM LTD of at least 2-2.5 cm. Conversion to DI was recommended to AS patients who developed PCI based on an algorithm incorporating life expectancy (LE): DI if LE > 15 years; shared decision-making for DI versus continued AS if LE 5–15 years; or continued AS/observation if LE < 5 years. AS patient outcomes were retrospectively reviewed, and 5- and 7-year rates of PCI-free (PFS), DI-free (DIFS) survival, and metastasis-free survival (MFS) were determined. Clinical predictors of these outcomes were identified in Cox regression multivariable analyses. Results A total of 373 patients without dialysis dependency or prior RCC treatment were seen over the 12-year study period and had follow-up of at least 3 months. Fewer than 3% (10 of 373) of these patients already had evidence of PCI at presentation and therefore underwent upfront treatment if medically fit. Of the remaining 363 SRM patients , 100% (97% of all SRM patients) deferred upfront treatment and were managed instead with AS. With median follow-up of 43 months, 105/363 (29%) AS patients developed PCI, and 77/363 (21%) underwent DI. The 5- and 7-year rates were 65.6% and 61.6% for PFS, and 74.6% and 71.0% for DIFS, respectively. One of 363 patients (0.3%) developed metastasis, and the 5- and 7-year MFS was 100% and 99.2%, respectively. PFS and DIFS were both significantly shorter with larger initial LTD, clear cell biopsy histology, and lower Charlson Comorbidity Index. On multivariate analysis, larger initial LTD and clear cell biopsy histology were independent predictors of both PFS and DIFS. Conclusions In among the largest single-center SRM AS series reported to date, and the first AS series in which the vast majority (97%) of all SRM patients elected AS rather than immediate treatment, our findings support that AS is oncologically safe and durably limits the need for invasive treatment in SRM patients who are PCI-free at presentation but otherwise unselected. Broad deferral of immediate treatment improves risk stratification of SRMs by revealing prognostic information that is commonly unknown at presentation related to tumor growth dynamics and histology. This approach thus focuses intervention on the minority subset of higher-risk SRM cases, while allowing most other SRM patients to avoid invasive treatment and its potential morbidity.